Transition form factors: gamma* plus p -> Delta(1232), Delta(1600) - Lu, Y.; Chen, C. [UNESP]; Cui, Z-F; Roberts, C. D.; Schmidt, S. M.; Segovia, J.; Zong, H-S (Amer Physical Soc, 2019)
Electroproduction form factors describing the gamma* p -> Delta(+)(1232), Delta(+)(1600) transitions are computed using a fully dynamical diquark-quark approximation to the Poincare-covariant three-body bound-state problem in relativistic quantum field theory. In this approach, the Delta(1600) is an analogue of the Roper resonance in the nucleon sector, appearing as the simplest radial excitation of the Delta(1232). Precise measurements of the gamma* p -> Delta(+)(1232) transition already exist on 0 <= Q(2) less than or similar to 8 GeV2, and the calculated results compare favorably with the data outside the meson-cloud domain. The predictions for the gamma* p -> Delta(+)(1600) magnetic dipole and electric quadrupole transition form factors are consistent with the empirical values at the real photon point, and extend to Q(2) approximate to 6m(p)(2), enabling a meaningful direct comparison with experiment once analysis of existing data is completed. In both cases, the electric quadrupole form factor is particularly sensitive to deformation of the Delta-baryons. Interestingly, while the gamma* p -> Delta(+)(1232) transition form factors are larger in magnitude than those for gamma* p -> Delta(+)(1600) in some neighborhood of the real photon point, this ordering is reversed on Q(2) greater than or similar to 2m(p)(2), suggesting that the gamma* p -> Delta(+)(1600) transition is more localized in configuration space.